Penguatan Cultural Awareness Guru Sejarah Se-Jawa Timur Melalui Kursus Silang Budaya Nusantara - Wahyudi, Deny Yudo; Jati, Slamet Sujud Purnawan; Wijaya, Daya Negri; Utari, Shela Dwi; Laili, Vita Sabrina Azda; Ananda, Labuda Shofiya (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
In addition to competence as an educator, cultural understanding and cultural awareness are also important for a history teacher to have. History teachers have an obligation to provide multicultural perspectives to their students. Indonesia, a country that consists of various ethnicities, cultures, and religions, requires history teachers to fulfil this obligation. Therefore, teachers must have a strong foundation and teach how these cultures live and coexist. Through the implementation of the cross-cultural course, this research aims to improve teachers' professional competence, foster, and strengthen their cultural awareness, and broaden their understanding of cross-cultural history materials. This study used a quantitative method with a one-group pretest-posttest design involving giving a pretest before socialization (treatment) and then conducting a posttest afterwards. In our treatment We involved lecturers from the Department of History, Universitas Negeri Malang, as well as the East Java history teachers. In this study, we measured cultural awareness using a questionnaire. Furthermore, we used t-test on SPSS 26 application to calculate validity, reliability, and analysis test. The results of this service showed that the cultural awareness of East Java history teachers increased after attending the training. In addition, the creation of infographic learning media has equipped the teachers with new skills.